Analisis Pemahaman Siswa terhadap Konsep Sudut dalam Pembelajaran Matematika di UPT SMP Negeri 14 Medan - Maria Lilis Sartika Waruwu; Jhelsi Damanik; Rosmelia Elsada Sinaga; Najwa Dwi Heryanti; Gazla Hilmia Yunanda Rangkuti; KMA Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Understanding the concept of angles is an essential part of learning geometry; however, it remains a common difficulty for students. This study aims to analyze students’ understanding of angle concepts in mathematics learning at UPT SMP Negeri 14 Medan. This research employed a descriptive quantitative approach, with data collected through observation and written tests. The sample consisted of 27 seventh-grade students selected using purposive sampling. Students’ understanding was analyzed based on four aspects: basic conceptual understanding, representation ability, computational ability, and application ability. The results showed that basic conceptual understanding was in the good category (81%), representation ability was in the low category (37%), computational ability was in the moderate category (67%), and application ability was also in the moderate category (70%). These findings indicate that students have a good understanding of basic concepts; however, they still experience difficulties in representing and applying these concepts optimally. Therefore, it is necessary to implement learning strategies that emphasize the development of representation skills and problem-solving abilities in order to enhance students’ understanding of angle concepts in a more comprehensive and meaningful way.